A Prospective, Comparative, Clinical Study to Evaluate the Safety and Efficacy of Two Different 0.1% Riboflavin Solutions Used in Collagen Crosslinking Treatment for Patients with Keratoconus - Brar S (Dove Medical Press, 2021)
Sheetal Brar, Sri Ganesh, Shilpa S Reddy, Nagesh BN, Dhwni Shahanand Department of Phaco-Refractive Surgery, Nethradhama Superspecialty Eye Hospital, Bangalore, Karnataka, IndiaCorrespondence: Sheetal BrarNethradhama Superspeciality Eye Hospital, 256/14, Kanakapura Main Road, 7th Block, Jayanagar, Bengaluru, Karnataka, 560070, IndiaTel +919591002092Email brar_sheetal@yahoo.co.inPurpose: To compare the safety and efficacy of 0.1% riboflavin in two different solutions which is used in corneal collagen crosslinking (CXL) for the treatment of keratoconus.Methods: This was a prospective, randomized, comparison study which included 100 eyes of 61 patients with progressive keratoconus who underwent CXL with riboflavin 0.1% solution as a photosensitizer, using the standard Dresden protocol of using 3mW/cm2 UV-A irradiation for 30 minutes which corresponds to a total energy of 5.4 J/cm2. The recruited patients were divided into 2 groups ie, Flavin Group and Peschke-D group by computer generated randomization. Postoperative examinations were conducted on 1 day, 1 month, 3 months, 6 months and 12 months after the crosslinking.Results: For both groups, the mean manifest spherical equivalent (SE), astigmatism, best corrected distance visual acuity, keratometry values, thinnest pachymetry values, demarcation line depth and endothelial cell density preoperatively and at postoperative 12 months were comparable with no statistically significant differences. At 12 months postoperatively, 62% of eyes in the Flavin group, and 68% of eyes in the Peschke-D group had postoperative manifest SE of within ± 1.00 D. During UV-A exposure, the cornea in the Flavin group showed intraoperative thinning of 112 microns (27%) as compared with a thinning of 108.12 microns (26.5%) observed in the Peschke group (p=1.67) from the initial pachymetry readings. No eye in either group had any immediate or long-term postop vision threatening complications such as infectious keratitis, corneal melt, non-resolving corneal oedema or endothelial decompensation.Conclusion: Both riboflavin solutions were equally safe and effective in the management of progressive keratoconus, and resulted in similar changes in terms of mean manifest spherical equivalent (SE), astigmatism, best corrected distance visual acuity, keratometry values, thinnest pachymetry values, demarcation line depth and endothelial cell density at the end of 12 months postoperatively.Trial Registration Number: Ctri/2019/11/021841 (Www.ctri.nic.in).Keywords: keratoconus, collagen cross linking, CXL, riboflavin, Flavin, Peschke